Analysis of Heat and Mass Transfer on MHD Peristaltic Flow through a Tapered Asymmetric Channel. (26th January 2015) - Kothandapani, M.; Prakash, J.; Pushparaj, V.
Abstract : This paper describes the peristaltic flow of an incompressible viscous fluid in a tapered asymmetric channel with heat and mass transfer. The fluid is electrically conducting fluid in the presence of a uniform magnetic field. The propagation of waves on the nonuniform channel walls to have different amplitudes and phase but with the same speed is generated the tapered asymmetric channel. The assumptions of low Reynolds number and long wavelength approximations have been used to simplify the complicated problem into a relatively simple problem. Analytical expressions for velocity, temperature, and concentration have been obtained. Graphically results of the flow characteristics are also sketched for various embedded parameters of interest entering the problem and interpreted.